The Thickness Changes of Anatomical Ornamental Monocotyledon Plant Leaves Affected by the Interactions between Plant Types and Light Intensity - Daningsih, Entin; Febriyanti, Inka; Mardiyyaningsih, Asriah Nurdini (Fakultas Pertanian Universitas Padjadjaran, 2024)
The different levels of light intensity affect the anatomical thickness of monocotyledon ornamental plant leaves. The aim of this research was to determine the anatomical thickness of several monocotyledon ornamental plant leaves under different light intensities. The research used a factorial complete randomized design with two main factors, namely plant type and different light intensity, repeated three times. The first factor was the plant type, which consisted of six plant species of monocotyledon ornamental plants which were Chlorophytum laxum, Dracaena reflexa, Rhoeo discolor, Aglaonema commutatum, Cordyline fruticosa and Hymenocallis littoralis. The second factor was light intensity, which consisted of high light intensity (open areas) and low light intensity (shaded areas). The observation was carried out on preserved leaf anatomy made using the paraffin method with modification. The observation variables were the total thickness of the leaf, upper and lower epidermis, mesophyll (for undifferentiated mesophyll), and palisade and sponge (for differentiated mesophyll). Data were analyzed using analysis of variance followed by the LSD test if the treatment was significant. Correlation tests were carried out between total leaf thickness and each leaf anatomical part under conditions of high and low light intensity. The results showed that the interaction between plant types and light intensity influenced the total thickness of the leaves, upper and lower epidermis, and palisade. The plant types independently influenced the mesophyll and sponges, while the light intensity independently influenced only the mesophyll but not the sponge thickness. Hymenocallis littoralis was the only plant that showed thicker under low light intensity, with an increase in the thickness of the upper and lower epidermis. The palisade mainly influenced leaf thickness changes in the differentiated mesophyll.